Treatment-free remission after two nilotinib consolidation durations in chronic myeloid leukemia treated with imatinib: Phase 3 ENESTPath results - Rea, Delphine; Kyrcz-Krzemien, Slawomira; Sportoletti, Paolo; Mayer, Jiří; Illes, Arpad; Angona Figueras, Anna; Kiani, Alexander; Charbonnier, Aude; Marinakis, Theodoros; Stenke, Leif; Steegmann, Juan Luis; Saglio, Giuseppe; et al. (Leukemia, 2026)
The phase 3 ENESTPath study investigated treatment-free remission (TFR) rates in patients with chronic Philadelphia chromosome-positive (Ph+) and/or BCR::ABL1+ chronic myeloid leukemia who had not achieved deep molecular response (DMR) after >2 years of imatinib treatment and were switched to nilotinib 300 mg twice daily (BID). After 24 months of treatment, patients with a stable DMR were randomized to either enter the TFR phase (Arm 1) or continue nilotinib consolidation for an additional 12 months and then enter the TFR phase if in stable DMR (Arm 2). The primary endpoint was the proportion of patients who remained in TFR (≥MR4.0 [BCR::ABL1IS ≤ 0.01%]) without molecular relapse at the end of 12 months. Of the 620 patients enrolled, 239 (38.5%) achieved stable MR4.0 and were randomized to Arm 1 (n = 120) or Arm 2 (n = 119). In the TFR phase, MR4.0 rates at 12 months (Arm 1: 31.9%, Arm 2: 37.5%; p = 0.383) and 24 months (Arm 1: 29.4%, Arm 2: 30.8%) revealed no differences in TFR success between 2 and 3 years of nilotinib. Irrespective of the consolidation duration, switching to nilotinib 300 mg BID provided the opportunity to achieve TFR if patients were unable to reach stable DMR with first-line imatinib.